(untitled) - Beniger, James R. (Cambridge, Mass., 1986)
This book is designed to be the synthetic work on the 'Information Society' and its origins, and by all rights it will be. It is beautifully done and is built to last...Everything about the book is intelligent
Keywords: Communication,Information technology,Information society,Giao tiếp,Công nghệ thông tin,Xã hội thông tin; Social aspects,Social aspects,Khía cạnh xã hội,Khía cạnh xã hội; United States,United States,Hoa Kỳ,Hoa Kỳ